(3fgGjI GdEOQGc aj OQGjI GdCadGcs - (3eMehO Hf eSYhO Hf eUdM GdaGQSj GdYdGej , bWH GdOjf , GdbWH GdTjQGRj,J (B710 (3g` s
(3ChdgG (B:s
(3CeG HYO MeOkG ddg aGWQ GdSehGJ ahb GdCQVjf aCJi bO cfJ HQgI ef GdReGf YGRakG Ydi Cf CMQQ dfaSi hdSGFQ GdENhGf ai Yde GdgjFI s
(3BNQgG (B:s
(3aQcH GdCadGc hGdJPcQI hGdeMUd hefJgi GdEOQGc hGdJHUQI adjNJe GdcJGH MGeOjf ddg JYGdi s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B187 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B20 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B407s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1985s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3Gdadcs